The Influence of Entrepreneurial Orientation, Market Orientation, Learning Orientation, and Government Support on MSME Performance: A Case Study of Coffee Shops in Jakarta - Panjaitan, Esther Elisabeth; Wahyuni, Sari (Amkop Management Accounting Review (AMAR), 2025)
The rapid growth of coffee shop MSMEs in Jakarta has intensified competition and increased the need for effective strategies to sustain performance and business continuity. This study aims to analyze key factors influencing the performance of coffee shop MSMEs by integrating entrepreneurial orientation, market orientation, learning orientation, innovation capability, and institutional government support. A qualitative descriptive approach with a multiple case study design was employed. Data were collected through in-depth interviews, direct observation, and document analysis of coffee shop MSMEs in South and East Jakarta, and analyzed using data reduction, data display, and conclusion drawing with triangulation. The findings indicate that entrepreneurial, market, and learning orientations play a significant role in shaping innovation capability, which enhances both financial and non-financial performance. Innovation capability serves as a mediating mechanism between strategic orientations and MSME performance, while government support acts as a complementary factor, although its utilization remains limited. These findings provide theoretical contributions and practical implications for MSME development and the sustainability of Jakarta’s coffee shop industry.